Meningkatkan kemampuan berpikir kritis matematis siswa SMP melalui penerapan pendekatan saintifik dengan model pembelajaran kooperatif tipe student teams achievement division (STAD) - Rahmah, Wulan Siti; Sugandi, Asep Ikin; Zanthy, Luvy Sylviana (IKIP Siliwangi, 2026)
This study aims to determine the effectiveness of implementing the scientific approach combined with the Student Teams Achievement Divisions (STAD) cooperative learning model on student’ learning mastery and the improvement of mathematical critical thinking skills in junior high school. The research employed a mixed-method design with a Convergent Parallel approach, in which quantitative and qualitative data were collected simultaneously. Quantitative data were obtained through pretetsts and posttests, while quantitative data were collected through student response questionnaires. The research subjects consisted of 30 seventh-grade students of class VII-A as the experimental group and 30 students of class VII-E as the control group. The result showed that the experimental group achieved an average posttest score of 27,73 with a mastery level of 93,33%, while the control group obtained an average of 16,73 with no students achieving mastery. These findings indicate that the learning outcomes of the experimental group were superior. In addition, students’ responses to the learning process were in the strong category, with a score of 78,55%.